Field surveys reveal physicochemical conditions promoting occurrence and high abundance of an invasive freshwater snail (Potamopyrgus antipodarum) - Michele D. Larson; Daniel Greenwood; Kara Flanigan; Amy C. Krist (Aquatic Invasions)
Environmental conditions promoting the occurrence and high abundance of non-native taxa are linked to critical stages of species invasions: establishment, whether a site can sustain a population of the non-native taxon, and impact, the extent to which the consequences of establishment negatively affect the invaded ecosystem. Using surveys across environmental gradients, we examined the physicochemical conditions associated with the occurrence and abundance of the invasive New Zealand mudsnail (Potamopyrgus antipodarum) and co-occurring native mollusks. Abundance of Potamopyrgus very strongly increased with stream width and conductivity (specifically with chloride, sulfate, potassium, and sodium ions). Also, Potamopyrgus were most likely to occur at sites with relatively low pH and water velocity and relatively high calcium ion concentration and abundance also slightly increased in these conditions. The physicochemical conditions indicate the characteristics of sites that are suitable for establishment and secondary spread of Potamopyrgus. Native mollusks differed from Potamopyrgus in the physicochemical conditions associated with abundance suggesting that variation among habitats could permit native mollusks to persist at larger geographic scales even if they often co-occur with Potamopyrgus. Abundance of native Physa moderately decreased with abundance of Potamopyrgus. Because abundance of Physa and Potamopyrgus responded oppositely to stream width and conductivity, the negative relationship between the abundance of these two taxa may be caused by contrasting responses to physicochemical conditions, acting alone or in concert with biotic interactions.